Dear Angelo: Digital Story - Prance, LJ (Ars Medica, 2023)
<div dir="auto" style="caret-color: #212121; color: #212121; font-family: Calibri; font-size: 16px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">Dear Angelo <div dir="auto" style="caret-color: #212121; color: #212121; font-family: Calibri; font-size: 16px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">By LJ Prance <div dir="auto" style="caret-color: #212121; color: #212121; font-family: Calibri; font-size: 16px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">Edited by Fraser Allen Best <div dir="auto" style="caret-color: #212121; color: #212121; font-family: Calibri; font-size: 16px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;"> <div dir="auto" style="caret-color: #212121; color: #212121; font-family: Calibri; font-size: 16px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">"Dear Angelo" is one of many stories of my transplant trip. I like to think of it as a conversation I may have had with my donor. <div dir="auto" style="caret-color: #212121; color: #212121; font-family: Calibri; font-size: 16px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">I chose the name "Angelo" as both a metaphor and a homage to a friend. <div dir="auto" style="caret-color: #212121; color: #212121; font-family: Calibri; font-size: 16px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">- dhanyavaad